Lichen planus pemphigoides erupting after COVID‐19 vaccination and infection, successfully treated with methotrexate - Josefin Andrén; Ismini Vassilaki; Philip Curman (Wiley, 2024)
Abstract We report a case of lichen planus pemphigoides (LPP) in a 36‐year‐old woman who presented bullous skin eruptions following both COVID‐19 infection and vaccination. The patient had a history of biopsy‐confirmed lichen planus since 2013 and had been previously investigated for suspected dermatitis herpetiformis since 2014, with inconclusive biopsy results. On two separate occasions, following her COVID‐19 vaccination and infection, she suffered the eruption of similar bullous lesions. A final diagnosis of LPP was established, believed to have been triggered by both the vaccination and the COVID‐19 infection. Treatment with prednisolone offered temporary relief, but sustained remission was achieved with methotrexate. This is, to our knowledge, the first documented case of LPP post‐COVID‐19 vaccination or infection.